2004
DOI: 10.1021/la0485778
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Attachment and Hybridization of DNA Oligonucleotides on Patterned Single-Walled Carbon Nanotube Films

Abstract: DNA oligonucleotides were covalently immobilized to prepatterned single-walled carbon nanotube (SWNT) multilayer films by amidation. SWNT multilayer films were constructed via consecutive condensation reactions creating stacks of functionalized SWNT layers linked together by 4,4'-oxydianiline. Aminated- or carboxylated-DNA oligonucleotides were covalently immobilized to the respective carboxylated or aminated SWNT multilayer films through amide bond formation using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 32 publications
(45 reference statements)
0
73
1
Order By: Relevance
“…37,38 It is for these reasons that recent attention has been focused on the covalent attachment of carbon nanotubes to surfaces. For example, Jung et al 6,22,40 has reported a novel method for producing high density carbon nanotube arrays through the formation of an amine terminated surface by treatment of a glass surface with an aminosiloxane followed by subsequent attachment of shortened carbon nanotubes via a condensation reaction between amine and carboxylic acid groups. These SWCNT layers have excellent surface adhesion because of their strong chemical bonding to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 It is for these reasons that recent attention has been focused on the covalent attachment of carbon nanotubes to surfaces. For example, Jung et al 6,22,40 has reported a novel method for producing high density carbon nanotube arrays through the formation of an amine terminated surface by treatment of a glass surface with an aminosiloxane followed by subsequent attachment of shortened carbon nanotubes via a condensation reaction between amine and carboxylic acid groups. These SWCNT layers have excellent surface adhesion because of their strong chemical bonding to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Krishna et al reported the synthesis of functionally engineered single -walled carbon nanotubes (SWNTs) -peptide nucleic acid (PNA) conjugates especially for nanoelectronic applications [77]. Jung et al demonstrated that the DNA strands can be covalently attached to immobilized SWNT multilayer films [78]. They showed that the SWCNTs multilayer films were constructed via consecutive condensation reactions creating stacks of functionalized SWCNTs layers linked together by dianiline derivatives.…”
Section: Cnt/dna-based Nanosensorsmentioning
confidence: 99%
“…The developer, a multistep route to the formation of covalently linked adducts of single-wall carbon nanotubes (SWNT) and deoxyribonucleic acid (DNA) sequence was reported by Baker et al [46]. In their report, the DNA molecules covalently linked to SWNTs are accessible to hybridization and strongly favored hybridization with molecules having complementary sequences compared with non-complementary sequences [78]. Recently, Zhang et al [79] synthesized a type of compound, MWCNTs-CONH-(CH 2 ) 2 -SH, via carboxylation, and investigated a thickness-tunable multilayer film DNA biosensor built layer-by-layer (LBL) covalent attachment of gold nanoparticles (AuNPs) and multi-walled carbon nanotubes on an Au electrode [46].…”
Section: Cnt/dna-based Nanosensorsmentioning
confidence: 99%
“…Various potential applications, including those in chemical and biochemical sensors [6][7][8], nanoelectronic and optoelectronic devices [9][10][11][12][13][14], have been widely explored. However, most of these potential applications require the chemical modification of carbon nanotubes with specific functionalities [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these potential applications require the chemical modification of carbon nanotubes with specific functionalities [15]. So far, a wide range of electrochemical active species, biological molecules and nanoparticles, including DNA [8,16,17], proteins [18][19][20][21], ferrocene [20,22,23], porphyrins [24,25] and CdS nanoparticles [26] have been exploited. In recent times, porphyrins have also been utilised in conjunction with single walled carbon nanotubes (SWCNT) in the construction of solar-harvesting arrays.…”
Section: Introductionmentioning
confidence: 99%